The State of female students’ reproductive health of the Pedagogical Institute - Меліков, Омар Якович; Шумлянський, Леонід Анатолійович; Квітко, Максим Олександрович; Кухта, Оксана Сергіївна; Кравченко, Віталіна Василівна (Pedagogy of Higher and Secondary Education, 2013)
Melikov O. J., Shumlyansky L. A, Kvitko M. O., Kuhta O. S., Kravchenko V. V. The State of female students’ reproductive health of the Pedagogical Institute. The analysis of the general and reproductive health current state of the I-II course female students of the Pedagogical Institute. There was revealed an insufficient level of students’ knowledge on the matters of the family’s role, love, culture of sexual behavior, prevention of teenage pregnancy, the precaution of sexually transmitted diseases and infections. The basic directions of work to improve reproductive health were proposed.